2020
DOI: 10.3390/v12040360
|View full text |Cite
|
Sign up to set email alerts
|

Structural Genomics of SARS-CoV-2 Indicates Evolutionary Conserved Functional Regions of Viral Proteins

Abstract: During its first two and a half months, the recently emerged 2019 novel coronavirus, SARS-CoV-2, has already infected over one-hundred thousand people worldwide and has taken more than four thousand lives. However, the swiftly spreading virus also caused an unprecedentedly rapid response from the research community facing the unknown health challenge of potentially enormous proportions. Unfortunately, the experimental research to understand the molecular mechanisms behind the viral infection and to design a va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
231
0
19

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(252 citation statements)
references
References 80 publications
2
231
0
19
Order By: Relevance
“…Very recently, the Cryo-EM structure of the SARS-CoV-2 spike protein in the prefusion conformation has been determined [30]. The biophysical and structural evidence suggested that SARS-CoV-2 may bind ACE2 with a much higher affinity than SARS-CoV [30].Although it has been clear that SARS-CoV-2 infects human cells through the binding of the RBD domain to the human ACE2 receptor [30][31][32][33][34], the molecular mechanism of the binding between the RBD protein and the ACE2 receptor is still unknown. Many questions remain to be answered.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, the Cryo-EM structure of the SARS-CoV-2 spike protein in the prefusion conformation has been determined [30]. The biophysical and structural evidence suggested that SARS-CoV-2 may bind ACE2 with a much higher affinity than SARS-CoV [30].Although it has been clear that SARS-CoV-2 infects human cells through the binding of the RBD domain to the human ACE2 receptor [30][31][32][33][34], the molecular mechanism of the binding between the RBD protein and the ACE2 receptor is still unknown. Many questions remain to be answered.…”
mentioning
confidence: 99%
“…Although it has been clear that SARS-CoV-2 infects human cells through the binding of the RBD domain to the human ACE2 receptor [30][31][32][33][34], the molecular mechanism of the binding between the RBD protein and the ACE2 receptor is still unknown. Many questions remain to be answered.…”
mentioning
confidence: 99%
“…We obtained a recently generated interactome of all the physical interactions between SARS-CoV-2 and human proteins based on the work by Korkin and colleagues [26]. In brief, the interactome contains both virus-virus and virus-host protein-protein interactions based on structural interaction modeling and established experimental knowledge.…”
Section: Interactome Model For Sars-cov-2/human Cell Interactionmentioning
confidence: 99%
“…Coexpression-based networks [27] were generated using the corto algorithm with default parameters, freely available on the CRAN repository of R packages [28], using the SARS-CoV-2/human interactome proteins derived from [26] and the largest human lung RNA-Seq dataset available from the GTEX consortium, which was generated from 427 patients gene expression profiles [29]. In brief, corto calculates a coexpression network for each protein and then removes indirect interactions using Data Processing Inequality [30], which has been shown to provide a more robust readout of single protein abundance alone [31].…”
Section: Coexpression-based Lung Networkmentioning
confidence: 99%
See 1 more Smart Citation